Outcome-based accountability regimes in OECD countries: a global policy model?. Issue 3 (3rd July 2021) - Högberg, Björn; Lindgren, Joakim
ABSTRACT: The global diffusion of outcome-based accountability in education is contested, with accounts of universal convergence being challenged by perspectives emphasising heterogeneity across different national or local contexts. This study uses data from PISA to explore, firstly, the spatial and temporal diffusion of accountability across OECD countries, and secondly, whether accountability is implemented as a single coherent regime. Using cluster analysis techniques, we find that most countries fall into a 'Thick' accountability regime, with widespread use of most forms of accountability tools. However, this regime is not fully coherent, with some countries relying more on horizontal, and others on vertical, forms of accountability. A sizeable minority of countries fall into a 'Thin' regime, in which most accountability tools are largely absent. We also find indications of convergence across countries over time. We conclude that while accountability in education is indeed widespread, and increasingly so, it is not a universally dominant regime.